Antioxidant Activity of Eight Tomato (Lycopersicon Esculentum L.) Varieties Grown in Algeria - Mostapha, Bachir Bey; Hayette, Louaileche; Zina, Mouhoubi (Journal of Food Technology Research, 2014)
The harmful effects of the free radicals on human organism could be inhibited by antioxidants of fruits and vegetables such as tomato. In the present work, the antioxidant contents as well as the antioxidant activity of eight tomato varieties grown in Algeria are evaluated. Ascorbic acid and carotenoid contents are assessed using spectrophotometric methods.The phenolic compounds extracted using solvents with different polarities (methanol, 50% methanol, ethanol, and 50% ethanol) have been determined using the Folin-Ciocalteu reagent. The antioxidant activities have been evaluated using the DPPH scavenging activity and the reducing power assays. Ascorbic acid content ranged between 7 and 16.7mg/100g while carotenoid concentration varied from 5.7 to 9.57mg/100g. The phenolic content varies according to the variety and the extraction solvent; pure alcohols (ethanol and methanol) allow better extraction than the diluted ones (50% ethanol and 50% methanol). Linear correlations are noted between the antioxidant activity and phenolic, carotenoid and lycopene contents. The results indicate that the samples present variations in their antioxidant substance amounts and antioxidant activity; this could be attributed to the varietal factor. The hybridisation between Joker and Marmande varieties, which present the highest phenolic and carotenoid amounts, respectively, could give another variety with a high antioxidant activity.